The Golden Age of Islam and Its Impact on European Technology: A Historical Analysis - Darek Hans (ENDLESS: INTERNATIONAL JOURNAL OF FUTURE STUDIES, 2023)
This study explores the profound influence of the Islamic Golden Age on the technological advancements in Medieval Europe. It investigates how the innovations and knowledge from the Islamic world, particularly between the 8th and 14th centuries, were transferred to and assimilated within European societies, thereby playing a pivotal role in shaping the technological landscape of Europe. The primary aim is to delineate the extent of Islamic contributions to European technology, addressing the historical narrative that often overlooks these influences. This research seeks to bridge the gap in historical understanding and acknowledge the intercultural exchanges that have significantly impacted the development of technology. Employing a historical-analytical method, the study analyzes primary and secondary sources, including historical texts, scientific manuscripts, and archaeological findings. This approach facilitates a comprehensive understanding of the technological exchanges between the Islamic world and Europe. Key findings reveal that various technological innovations, such as advancements in mathematics, astronomy, engineering, and medicine, originated from the Islamic world and were instrumental in European technological progress. The study highlights specific instances of knowledge transfer, such as through the translation movement in Al-Andalus and the Crusades, which introduced Europe to a wealth of Islamic scholarly works and inventions. The findings underscore the importance of recognizing the Islamic Golden Age's contributions to European technology, challenging the Eurocentric view of history and science. This research contributes to a more inclusive historical narrative and underscores the value of intercultural knowledge exchange in technological advancement.